Medical educators’ perspectives on the barriers and enablers of teaching public health in the undergraduate medical schools: a systematic review - Nurhira Abdul Kadir; Heike Schütze (Global Health Action, 2022)
Background Having relevant public health content in the undergraduate medical curriculum is critical to preparing medical doctors for emerging health issues and increased public health roles. Medical educators are central to this effort. Objective This systematic review synthesises the most relevant and up-to-date evidence on medical educators’ perspectives regarding the barriers and enablers on incorporating public health teaching in the undergraduate medical curricula. Methods Seven databases were searched for articles published between 1 January 2010 and 31 December 2021. Articles were included if they were available in full-text English or Indonesian language, peer-reviewed, and focused on medical educators’ perspectives on teaching public health in the undergraduate medical curricula. Findings were integrated to answer the review question using thematic analysis. Results Twenty-nine articles were included in the final review. Three major themes emerged: (i) space in the medical curricula, (ii) confidence/capabilities of medical educators, and (iii) institutional support. Overcrowded curricula, lack of consensus about the scope and level of public health to incorporate into teaching, ensuring the quality and the relevance of content with what is required in real practice, as well as inadequate institutional support are major challenges in teaching public health to medical students. Conclusions Integrating public health into other subjects is largely seen as a solution. This requires strong institutional support in the form of financial, logistic, and technical support; structured training for medical educators on how to incorporate the content into their subjects; and a recognition of the important role that public health educators play.